Kalahari skinks eavesdrop on sociable weavers to manage predation by pygmy falcons and expand their realized niche. (2nd June 2020) - Lowney, Anthony M; Flower, Tom P; Thomson, Robert L
Abstract: Eavesdropping on community members has immediate and clear benefits. However, little is known regarding its importance for the organization of cross-taxa community structure. Furthermore, the possibility that eavesdropping could allow species to coexist with a predator and access risky foraging habitat, thereby expanding their realized niche, has been little considered. Kalahari tree skinks ( Trachylepis spilogaster ) associate with sociable weaver ( Philetairus socius ) colonies as do African pygmy falcons ( Polihierax semitorquatus ), a predator of skinks and weavers. We undertook observational and experimental tests to determine if skinks eavesdrop on sociable weavers to mitigate any increase in predation threat that associating with weaver colonies may bring. Observations reveal that skinks use information from weavers to determine when predators are nearby; skinks were more active, more likely to forage in riskier habitats, and initiated flight from predators earlier in the presence of weavers compared with when weavers were absent. Playback of weaver alarm calls caused skinks to increase vigilance and flee, confirming that skinks eavesdrop on weavers. Furthermore, skinks at sociable weaver colonies were more likely to flee than skinks at noncolony trees, suggesting that learning is mechanistically important for eavesdropping behavior. Overall, it appears that eavesdropping allows skinks at colony trees to gain an early warning signal of potential predators, expand their realized niche, and join communities, whose predators may otherwise exclude them. Abstract : Kalahari tree skinks associating with the enormous colonial nest of sociable weavers can eavesdrop on weaver alarm calls to avoid predation from pygmy falcons and forage in riskier habitat. When with weavers, skinks bask and forage in the open, fleeing when weavers alarm. These individuals were more likely to flee than skinks at noncolony trees, suggesting that eavesdropping is learned. Eavesdropping allows skinks at colony trees to expand their realized niche and avoid predation.